How changes in nutrition have influenced the development of allergic diseases in childhood - Peroni Diego G; Bonomo Beatrice; Casarotto Serena; Boner Attilio L; Piacentini Giorgio L (BMC, 2012)
Abstract The increasing prevalence of allergic diseases in childhood in the last decades could be linked to concomitant dietary changes, especially with the modified and lower consumption of fruit, vegetables and minerals. The consumption of these foods by pregnant women and children in the first years of life seems to be associated with a reduced risk of asthma and related symptoms. Foods that can prevent the development of wheezing through their antioxidant effects contain vitamin C and selenium; blood levels of these elements correlate negatively with the risk of wheezing. Intake of vitamin E during pregnancy also appears to be correlated with a reduced risk of wheezing for the unborn child. Similarly, low intake of zinc and carotenoids by pregnant women is associated with an increased risk of wheezing and asthma in childhood. Fiber also has anti-inflammatory properties and protective effects against allergic diseases such as atopic dermatitis and asthma. The consumption of fat influences the development of the airways. Populations in Western countries have increased their consumption of n-6 PUFAs and, in parallel, reduced n-3 PUFAs. This has led to decreased production of PGE2, which is believed to have a protective effect against inflammation of the airways. Conflicting hypotheses also concern vitamin D; both an excess and a deficiency of vitamin D, in fact, have been associated with an increased risk of asthma. Further studies on the role of these substances are necessary before any conclusions can be drawn on a clinical level. Astratto La crescente prevalenza negli ultimi decenni delle malattie allergiche in età pediatrica potrebbe essere legata a concomitanti cambiamenti nella dieta, in particolare alla minore e modificata introduzione di frutta, verdura e minerali. Il consumo di questi alimenti da parte delle donne in gravidanza e dei bambini nei primi anni di vita sembra essere associato ad un ridotto rischio di asma e di sintomi correlati. Gli alimenti che possono prevenire lo sviluppo di respiro sibilante (wheezing) attraverso i loro effetti antiossidanti contengono vitamina C e selenio; i livelli ematici di questi elementi sono correlati negativamente con il rischio di wheezing. Inoltre l'assunzione di vitamina E durante la gravidanza sembra essere correlato con un rischio ridotto di respiro sibilante per il nascituro. Allo stesso modo, basso apporto di zinco e di carotenoidi in donne in gravidanza è associata ad un aumentato rischio di wheezing e asma nell'infanzia. Anche le fibre hanno proprietà anti-infiammatorie ed effetti protettivi contro le malattie allergiche come la dermatite atopica e l'asma. Il consumo di grassi influenza lo sviluppo delle vie aeree. Le popolazioni dei paesi occidentali hanno aumentato il loro consumo di n-6 PUFA e, parallelamente, ridotto n-3 PUFA. Ciò ha portato alla diminuzione della produzione di PGE2, che si ritiene abbia un effetto protettivo contro l'infiammazione delle vie aeree. Ipotesi contrastanti riguardano la vitamina D, sia un eccesso che una carenza di vitamina D, infatti, sono stati associati ad un aumentato rischio di asma. Ulteriori studi sul ruolo di queste sostanze sono necessari prima di trarre conclusioni sul piano clinico.